Cognitive and cerebral perfusion outcomes following interventional revascularization in individuals with chronic middle cerebral artery occlusion - Yin, Liang; Sui, Pingli; Li, Qianqian; Xu, Juanjuan; Xu, Jiali; Chen, Xianwen (Frontiers in Neurology, 2025)
BackgroundChronic occlusion of the middle cerebral artery (MCAO) is frequently underdiagnosed due to mild or insidious clinical manifestations. Despite this, individuals with chronic MCAO are at an increased risk of cerebral infarction and progressive cognitive impairment. This study aimed to assess the efficacy of interventional revascularization therapy in comparison to standard medical treatment, with a focus on neurological and cognitive outcomes.MethodsFifty-five patients diagnosed with chronic MCAO were allocated to either a medication group or an interventional surgery group. Neurological status and cerebral perfusion parameters, including cerebral blood flow (CBF), time-to-maximum (Tmax), mean transit time (MTT), and cerebral blood volume (CBV) were assessed. Cognitive performance was assessed using the Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE). Post-treatment and follow-up data were collected and analyzed.ResultsAmong the 29 participants in the interventional surgery group, successful recanalization was achieved in 26 cases, while three procedures were unsuccessful. Improvements in neurological deficits were observed in both groups. However, significant enhancements in cerebral perfusion parameters (CBF, Tmax, and MTT) and cognitive scores (MoCA and MMSE) were identified only in the interventional group. No statistically significant changes in cerebral perfusion or cognitive performance were observed in the medical therapy group.ConclusionInterventional revascularization therapy was associated with improved cerebral perfusion and enhanced cognitive outcomes compared to medical management in individuals with chronic MCAO.